Stigmatization Against Tuberculosis (Tb) and Leprosy Patient(S) in Taraba North Senatorial District: Counseling as a Remedy - Adamu Musa; Mohammed Sanusi Yuguda; Yusuf Rebecca Auta; Tanimu Joseph (Zien Journals, 2022)
Stigmatization against Tuberculosis (TB) and Leprosy patients by the society affected them from exercising their rights as it relate to health care services and liberty of life as enshrine. This study “stigmatization against Tuberculosis (TB) and Leprosy patient(s) in Taraba North senatorial district” revealed the harsh experiences often face by those infected with this disease in recent time either by caregiver, family relative, health attendees’ e.t.c. which often led them being traumatized, there condition worsen and later lead to their death. This study evaluated the needs for counseling for those stigmatized as preventive and corrective measures for the downtrodden. The findings also revealed that caregiver, family relative, health attendees’ e.t.c rendering services to those affected by TB and leprosy experienced the same gesture of stigma within the society. The fear of being infected is evidence undermining caregiver, family relative, health attendees experiences in-terms of rendering services to those affected with the disease. The literature reviews of this study demonstrated understanding about the concepts of stigma, TB and Leprosy among the population. Random sampling procedures were employed for sampling of respondents for this study, a qualitative and quantitative approach were also employed. One hundred and four (104) respondents were randomly selected from the population which includes twenty six (26) previous and present patients of TB and leprosy, Twenty eight (28) health attendees, eighteen (18) care-givers, and thirty two (32) community members from Taraba North senatorial district comprising of six Local Government Areas namely Ardo-Kola, Jalingo, Karim- Lamido, Lau, Yorro and Zing. The Data for this study were analyzed using descriptive statistics and Pearson's Product Moment Correlation Coefficient (PPMC). Same instrument was used in analyzing the relationship that exists between counseling and stigmatized TB and Leprosy patients. The study revealed that counseling services for (Patients, caregiver, family relative, health attendees) are important requirement in the attainment of effective care for those stigmatized (TB and Leprosy Patients) which can help in improving their mental state and health condition.
Keywords: Stigmatisation; Counseling; Tuberculosis; Leprosy